PARACOCCIDIOIDOMYCOSIS IN A RENAL TRANSPLANT RECIPIENT - GÓES, Heliana Freitas de Oliveira; DURÃES, Sandra Maria Barbosa; LIMA, Caren dos Santos; SOUZA, Mariana Boechat de; VILAR, Enoi Aparecida Guedes; DALSTON, Marcos Olivier (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Paracoccidioidomycosis (PCM) is the most common endemic mycosis in Latin America. The etiological agents, which comprise two species, Paracoccidioides brasiliensis and P. lutzii, are thermodimorphic fungi that usually affect previously healthy adults. They primarily involve the lungs and then disseminate to other organs. Such mycosis is rare in organ transplant recipients; there have been only three cases reported in literature, until now. We report a case of PCM in a renal transplant recipient with an unusual dermatological presentation.